Synthesis and Characterization of D-A-D Type Chromophore DSeBT - Tong1, Junfeng; An2, Lili (Asian Journal of Chemistry, 2013)
A donor-acceptor-donor (D-A-D) type crystallization near infrared (NIR) absorbing chromophore DSeBT with a band gap of 0.84 eV is synthesized via palladium-catalyzed Stille coupling reaction. In thin film, the absorption region of DSeBT is from 300 and 1459 nm with the absorption peaks located at 380 and 1028 nm, while its photoluminescence peak in chloroform solution is observed at 1210 nm. The HOMO and LUMO energy levels of DSeBT are estimated at -4.86 and -4.02 eV, respectively. Furthermore, the thermal results reveal that DSeBT has a good thermal stability with decomposition temperature over 320 ºC and a very sharp crystallization peak at 174 ºC during the cooling run.